A STUDY ON WORK SAFETY FOR EMPLOYEES IN DIAGNOSTIC SERVICES – RECOMMENDATIONS TO IMPROVE WORK SAFETY - ANUPRIYA ASAITHAMBI; PRIYA BANTHAVI SIVA SUBRAMANIAN; CHITRA RAJALAKSHMI PARTHASARATHY (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: To assess the effectiveness of the safety training program in preventing occupational hazards for workers in clinical laboratories and radiology and make recommendations. Methods: During the course of 2 months, health-care workers in radiology and central laboratory, including doctors, radiology technicians, and laboratory technicians were the subjects of this prospective analytical study. The design of the study was based on the lean methodology. Every participant received a structured questionnaire. Next, they attended a workshop on workplace safety, after which they completed a post-test questionnaire. Results: Of the participants in the study, 38% were between the ages of 31 and 40. Almost 56% had completed their postgraduation education, and 62% had worked for more than 10 years. Of these, 42% were laboratory technicians, 24% were from the phlebotomy and radiology departments, and there was a highly significant difference (p<0.01) in the participants’ awareness of OSH perceptions as well as prevention of physical risks and injury. Conclusion: The laboratory workers’ knowledge and actions addressing the prevention of laboratory hazards and safety environmental condition dangers have been improved by the training safety program.